Formation of Protein Film from Chickpea Dha) - Mohamed, Suhaila; Abdullah, Norlia (1988)
The optimum conditions for the formation of chickpea dhal protein film and the characteristics of the films were studied. Optimum yield of protein films was obtained form chickpea dhal at bean: water ratios of 1:5 to 1: 7 and in the pH range of 9.0 to 10. O. The chickpea protein films were darker and more brittle than soybean protein films.